2010
DOI: 10.1017/s0022112010004738
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of bead formation, filament thinning and breakup in weakly viscoelastic jets

Abstract: The spatiotemporal evolution of a viscoelastic jet depends on the relative magnitude of capillary, viscous, inertial and elastic stresses. The interplay of capillary and elastic stresses leads to the formation of very thin and stable filaments between drops, or to ‘beads-on-a-string’ structure. In this paper, we show that by understanding the physical processes that control different stages of the jet evolution it is possible to extract transient extensional viscosity information even for very low viscosity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
116
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(129 citation statements)
references
References 23 publications
10
116
0
3
Order By: Relevance
“…In the nonlinear region the value of strain rate experienced by the Lagrangian element reaches a plateau at✏ P = 1.1⇥10 4 s 1 which corresponds to a constant critical Weissenberg number, W i ⌘ ⌧ E✏ = 2/3. These results are in good agreement with both previous experiments and solutions/simulations in the literature for the nonlinear behavior of viscoelastic filaments during the jet breakup [33,68,70,75,76].…”
Section: Rayleigh-ohnesorge Jetting Extensional Rheometry (Rojer)supporting
confidence: 92%
See 2 more Smart Citations
“…In the nonlinear region the value of strain rate experienced by the Lagrangian element reaches a plateau at✏ P = 1.1⇥10 4 s 1 which corresponds to a constant critical Weissenberg number, W i ⌘ ⌧ E✏ = 2/3. These results are in good agreement with both previous experiments and solutions/simulations in the literature for the nonlinear behavior of viscoelastic filaments during the jet breakup [33,68,70,75,76].…”
Section: Rayleigh-ohnesorge Jetting Extensional Rheometry (Rojer)supporting
confidence: 92%
“…The appearance of large satellite droplets must be minimized in ROJER applications as they modify the desired extensional thinning kinematics. Numerical studies by Ardekani et al [76] explored nonlinear jet thinning and approach to breakup using the Giesekus constitutive equation to describe the complex fluid rheology. They showed that there is a narrow band of wavenumbers for which periodic forcing of the jet will not lead to formation of satellite droplets and this is the optimal range for elongational rheometry.…”
Section: Drop Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…The filament thinning and break up of viscoelastic fluid jets are governed by different physical processes involving inertio-capillary, viscous and elastic forces. The relative importance of these forces can be determined in terms of two dimensionless parameters defined as the ratios of the time scales characterizing each process [65,66]. The Ohnesorge number (Oh) is defined as the ratio of the viscous time scale [46] and applied to the monodisperse PMMA samples dissolved in Asahiklin.…”
Section: Resultsmentioning
confidence: 99%
“…The beads-on-string structure was studied by Clasen et al [9] using the Oldroyd-B model. Ardekani et al [4] investigated the dynamics of beads-on-string structure and filament thread for weakly viscoelastic jets by using the Giesekus constitutive equation and they compared the results to those of the Oldroyd-B model. Bhat et al [6] examined formation of beads-on-a-string structures and found that there are sub-satellite beads in their experiments.…”
Section: Introductionmentioning
confidence: 99%